The Malay Standard Framework (KSBM) as a measure of Malay writing mastery in third form activity books - Abd. Nasir, Siti Noridayu; Abdul Halim, Hazlina (Nun Gemilang Enterprise, 2023)
Mastery in writing skills is an important for students who will seat the end of year exams at school. This is because the weighting of the marking in the Malay subject is the writing of reviews and essays. Therefore, this study focuses on the title of reviews and essays in Big Ideas Form Three in Malay subject activity books. This activity books is used by the Imtiyaz Tuition Centre in Putrajaya to train students at the third level for five month from early January to Mei. In fact, this study is also to identify an extend to which essay titles related to current issues can measure the level of mastery in third level essay writing by tuition students. The findings of the study showed that five respondents tend to answer review questions that have visuals and text as their writing ideas. Therefore, KBSM can an applied in measuring the level of Malay language review writing ability of five study respondents. This I because, the measurement of marks shows the ability of students who are excellent or still weak in writing reviews. It is hoped that this study can helps an improve the level of students skill in the future get good marks and grades in final exams at school.